Enniscorthy Castle - Nicholl, Andrew, 1804-1886; Hall, S. C., Mrs., 1800-1881 (1840)
View of Enniscorthy Castle with a group of peasants and a horse and cart in the foreground.
Title inscribed l.r. on sheet.
Attributed to Andrew Nicholl.
Catalogue of Irish Topographical Prints and Original Drawings / Rosalind M. Elmes ; New edition revised and enlarged by Michael Hewson - Dublin : Malton Press, 1975
Ireland: its scenery, character, &c / Mr. & Mrs. S. C. Hall - London: How and Parsons, 1841-43.
Keywords: Castles & Palaces -- Ireland -- Wexford (County) -- 1830-1840; Enniscorthy (Wexford, Ireland); Pencil drawings -- Irish -- 1830-1840.